Impact of a training intervention on use of antimicrobials in teaching hospitals - Akter, Seikh Farid Uddin; Heller, Richard D.; Smith, Anthony J.; Milly, Afia F. (Open Learning on Enteric Pathogens, 2009)
Background: Antimicrobials are often used inappropriately in paediatric wards of medical college hospitals in Bangladesh. Most of the antimicrobials are prescribed based on clinical grounds–signs and symptoms. This intervention study assessed the effectiveness of a training intervention on antimicrobials prescribing by physicians in paediatric wards of tertiary care level hospitals. Methodology: This study was conducted at medical college hospitals in Bangladesh during the period from 1998 through 2000. The pre-intervention survey of antimicrobial use was conducted during 1998 in five hospitals. The post-intervention survey was conducted after the interactive training during the succeeding year in three of the original five hospitals, of which one was the intervention hospital and two control hospitals. A total of 3,466 admitted paediatric patients' treatment charts (2,171 in the pre-intervention and 1,295 in the post-intervention surveys) were reviewed. Results: The most commonly used antimicrobials were ampicillin, gentamicin, amoxicillin, cloxacillin and ceftriaxone. Appropriate antimicrobial therapy for the most common infectious diseases, pneumonia and diarrhoea, increased by 16.4% and 56.8% respectively in the intervention hospital compared with the two control hospitals and these improvenmts were significant (p = < 0.001 and p = 0.002, for pneumonia and diarrhoea respectively). Conclusions: An interactive, focussed educational intervention, targeted at physicians, appears to have been effective in improving appropriate antimicrobial prescribing for the most common paediatric infectious diseases in a medical college hospital in Bangladesh.